Computer and Information Science - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the edited proceedings of the 16th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2017), which was held on May 24-26, 2017 in Wuhan, China. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the various fields of computer science, share their experiences and exchange new ideas and information. The research results included relate to all aspects (theory, applications and tools) of computer and information science, and discuss the practical challenges encountered and the solutions adopted to solve them. The work selected represents 17 of the most promising papers from the conference, written by authors who are certain to make further significant contributions to the field of computer and information science.
Big Data and IoT for U-healthcare Security -- Retrospection and Perspectives on Pragmatic Software Architecture Design: An Industrial Report -- Distributed Coding and Transmission Scheme for Wireless Communication of Satellite Images -- Experimental Evaluation of HoRIM to Improve Business Strategy Models -- Combining Lexicon-Based and Learning-Based Methods for Sentiment Analysis for Product Reviews in Vietnamese Language -- Reducing Misclassification of True Defects in Defect Classification of Electric Board -- Virtual Prototyping Platform for Multiprocessor System-on-Chip Hardware/Software Co-design and Co-verification -- A Data-mining Model for Predicting Low Birth Weight with a High AUC -- A Formal Approach for Maintaining Forest Topologies in Dynamic Networks -- A Multicriteria Approach for Selecting the Optimal Location of Waste Electrical and Electronic Treatment Plants -- Localization Strategy for Island Model Genetic Algorithm to Preserve Population Diversity -- HM-AprioriAll Algorithm Improvement Based on Hadoop Environment -- Architecture of a Real Time Weather Monitoring System in a Space Time Environment Using Wireless Sensor Networks -- Mobile Application Development on Domain Analysis and Reuse-Oriented Software (ROS) -- A Transducing System between Hichart and XC on a Visual Software Development Environment -- Development of and Interface for Volumetric Measurement on a Ground-Glass Opacity Nodule -- Efficient Similarity Measurement by the Combination of Distance Algorithms to Identify the Duplication Relativity.
Keywords: Computational intelligence; Artificial intelligence; Business information services; Computer networks .; Electronic data processing -- Management; Computational Intelligence; Artificial Intelligence; Business Information Systems; Computer Communication Networks; IT Operations